Comparative study of historical and scientific documentation of the paintings in the Querciola Tomb in Tarquinia. - Ceccarelli, S.; Francucci, M.; Ferri De Collibus, M.; Ciaffi, M.; Fantoni, R.; Carmagnola, R.; Adinolfi, G.; Guarneri, M. (Journal of Cultural Heritage, 2023)
• First comparative study of historical and modern documents of the Etruscan Querciola tomb. • Ancient drawings dated back to the end 19th and the early 20th centuries. • Prototypal laser scanner for 3D colour digitalisation of the tomb. • Creation of a documentation archive for conservative monitoring purposes. This paper presents the preliminary results of an ongoing multidisciplinary study carried out in the Etruscan tomb called Querciola with a twofold aim: on one hand, the comprehension of the storytelling of its unique paintings, on the other, the collection and analyses of documentation for monitoring the state of preservation of the tomb and the paintings over the years. The investigations were carried out by studying historical and archival sources, ancient hand drawings and acquiring 3D-coloured models obtained by using a high-definition 3D laser scanner prototype. The ancient drawings were made with different techniques (pencil, tempera , watercolours) by several artists from 1831 to 1935 as a means of documentation, also by drawing on paper on a scale of 1:1. However, the reliability of graphic and colour transpositions is not entirely certain, raising art-historical doubts about the original appearance of the paintings and the presence of personal contributions of individual artists in each drawing. For this reason, the 3D model acquired by the laser scanner constitutes a very useful tool for scientific and reliable documentation, which can be also considered as a starting point for long-term monitoring. The acquired 3D models provided the accurate digitalisation of the entire tomb, collecting both colorimetric and structural information, without the influence of the environmental illuminating conditions, for conservative, scientific and educational purposes. The post-processing of the images permitted the analysis of the state of health of the site and of its paintings, as well as improving the readability of some elements of the pictorial cycle of the tomb that are now barely visible. The preliminary results of this study demonstrated the importance of using multidisciplinary resources and the cooperation between scholars coming from different fields, for the comprehension and the recovery of partially lost paintings, improving the possibility to better understand iconography of the Etruscan art.